ENHANCING TRACKING PRACTICES IN THE MALAYSIAN FREIGHT FORWARDING INDUSTRY - Jamaluddin, Zaharuzaman; Jahari, Nor Azah; Abdullah, Sharifah Hilmi Syed; Muslim, Norjiah (International Journal of Business and Management Future, 2021)
Freight forwarding is the movement of all intermodal commodities on behalf of shippers. Although the freight forwarding industry's contribution to a country's national output may not be as competitive as other sectors, the role that this industry plays in supporting an economy's activity cannot be underestimated. Furthermore, the stiff competition in the freight forwarding industry requires companies to continue to excel to survive and compete with the competitors. Thus, the purpose of this paper is to assess current literature and practices in the freight forwarding industry regarding tracking practices. Furthermore, it is expected that the documentation, freight readiness, route and technology capabilities will serve as a foundation for more effective operations and practices in Malaysia, ensuring the freight forwarding industry's sustainability. The study contributes to the body of knowledge on freight forwarding performance and can assist managers in reacting appropriately to create cost-effective logistic solutions.